Mesoporous carbon supported praseodymium oxide catalyst as well as preparation method and application thereof
Through the preparation of mesoporous carbon-laden priseodymium oxide catalyst, the problem of difficult control of the structure and particle size of rare earth priseodymium oxide nanomaterials is solved, and the uniform dispersion and particle size uniformity of praseodymium oxide nanoparticles are achieved, which significantly improves the cycle stability and catalytic performance of lithium sulfur batteries.
Patent Information
- Application Number
- CN202411924143.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing rare earth praseodymium oxide nanomaterials are difficult to control, which makes it impossible to widely promote in catalytic applications.
Mesoporous carbon-supported praseodymium oxide catalysts are prepared with mesoporous carbon-supported praseodymium oxide nanoparticles evenly distributed in the mesoporous pore wall of the carbon support through triblock copolymer self-assembly technology.
The uniform dispersion of praseodymium oxide nanoparticles and uniform particle size are achieved, which significantly improves the cycle stability of lithium-sulfur batteries and has excellent catalytic performance.
Smart Images

Figure CN119701924A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rare earth catalysts, and in particular to a mesoporous carbon-supported praseodymium oxide catalyst, a preparation method and application thereof. Background Art
[0002] The unique electronic structure of rare earth elements has attracted people's continuous attention for their optical, electrical and magnetic properties. They are widely used in cutting-edge science and technology and military fields, covering high-tech industries such as rare earth permanent magnets, luminescence, hydrogen storage, catalysis, precision ceramics, metallurgy, and new energy. Rare earths are crucial to modern technology and are an indispensable raw material for many high-tech products. They are known as "industrial vitamins" and are important strategic resources for promoting my country's high-end materials and precision manufacturing industries to emerge in international competition. Therefore, the development and utilization of rare earth resources are of great significance to the country's economic development and national defense security.
[0003] At present, the most common rare earth compounds are mainly oxides, among which praseodymium-based rare earth oxides have high electrical conductivity and oxygen ion mobility. They are one of the most widely studied and used rare earth materials. Their development and synthesis can provide important material basis and material support for the development of industries such as catalysis, cutting-edge manufacturing, and electronic materials. The preparation methods of rare earth praseodymium oxide include hydrothermal / solvothermal method, microwave-assisted method, thermal decomposition method, sol-gel method, coprecipitation method and combustion method, among which oxalic acid precipitation method and ammonium bicarbonate precipitation method are mainly used in industry. The chemical precipitation method can obtain praseodymium oxide with intact crystal form, but it is easy to form agglomerates during the synthesis process, and it is difficult to obtain nano-sized praseodymium oxide, which limits the effective utilization rate of praseodymium oxide in many fields, especially in the field of catalysis, and hinders the development of this material. Since praseodymium oxide nanoparticles have high surface energy and are easy to aggregate to form larger particles, special dispersion technology and particle size control methods are usually required to synthesize nano-sized praseodymium oxide materials. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is that the structure and particle size of the existing rare earth praseodymium oxide nanomaterials are difficult to control, resulting in the inability to widely promote them in catalytic applications. The present invention provides a mesoporous carbon-supported praseodymium oxide catalyst, a preparation method and its application, wherein the rare earth praseodymium oxide nanoparticles in the catalyst are evenly dispersed and have uniform particle size, and the catalyst can accelerate the sulfur reduction reaction of lithium-sulfur batteries and significantly improve the cycle stability of lithium-sulfur batteries.
[0005] To achieve the above object, the present invention provides a method for preparing a mesoporous carbon-supported praseodymium oxide catalyst, comprising the following steps:
[0006] The triblock copolymer is used as a template, ethanol is used as a solvent, a low molecular weight phenolic resin produced by prepolymerization of phenol and formaldehyde is used as an organic precursor to provide a carbon source, and praseodymium salt hydrate is used as a metal source, and a mixed solution is obtained by stirring uniformly at a certain temperature;
[0007] The ethanol in the mixed solution is volatilized at a low temperature, and the carbon source and the metal source are co-assembled with the block copolymer through hydrogen bonding during the volatilization of the solvent ethanol to form a metal-polymer mesostructure, and then thermal polymerization occurs at a high temperature to fix the ordered mesophase of the metal-polymer;
[0008] The block copolymer is removed by low-temperature calcination, and then carbonized at high temperature to obtain a stable mesoporous carbon-supported rare earth praseodymium oxide catalyst, in which praseodymium oxide nanoparticles are uniformly distributed in the mesoporous pore walls of the carbon carrier.
[0009] Mesoporous carbon-supported praseodymium oxide catalyst has a highly ordered two-dimensional hexagonal mesostructure.
[0010] Furthermore, the triblock copolymer is F127, and F127 is (HO·(C2H4O) m ·(C3H6O) n ·H), the amount of F127 added is 0.8-1.5 g, the amount of ethanol added is 10-50 mL, the amount of PF added is 5-8 g, and the praseodymium salt hydrate is Pr(NO3)3·6H2O, and the amount added is 324 g.
[0011] Furthermore, the carbon source and the metal source co-assemble with the block copolymer through hydrogen bonding during the volatilization of the solvent ethanol. Specifically, under the induction of ethanol, the carbon source and the metal source assemble into an ordered mesoscopic structure, and then undergo thermal polymerization to stabilize the mesoscopic phase. The heating rate is 1-5 °C min -1 The temperature of ethanol volatilization is controlled at 30-50°C, the time of ethanol volatilization is controlled at 8-24h, the thermal polymerization temperature is 80-100°C, and the thermal polymerization time is controlled at 24-48h.
[0012] Furthermore, F127 is first mixed with ethanol and stirred for 0.5 to 2 hours, and then an ethanol solution containing praseodymium salt is added. After the above liquids are evenly mixed, PF is added dropwise, followed by stirring for 0.5 to 1 hour. The reaction temperature of the above solution is controlled at 30 to 50°C.
[0013] Furthermore, the block copolymer is removed by low-temperature calcination, and then a stable mesoporous carbon-supported rare earth praseodymium oxide catalyst is obtained by further high-temperature carbonization, wherein the calcination atmosphere is N2 and the heating rate is 1-5°C min -1 The temperature for removing the block copolymer is 200-400°C and maintained for 2-5 hours, and the temperature for high-temperature carbonization is 500-800°C and maintained for 1-3 hours.
[0014] Furthermore, a praseodymium salt precursor solution is prepared, 324 g of praseodymium salt is configured into 5-10 mL of ethanol solution, and ultrasonicated for 5-30 minutes to obtain a uniform praseodymium salt ethanol solution.
[0015] In a preferred embodiment of the present invention, a mesoporous carbon-supported praseodymium oxide catalyst prepared by the above method is provided, wherein the particle size of praseodymium oxide on the catalyst is within 10 nm and is uniformly distributed in the mesoporous pore walls of the carbon carrier.
[0016] In another preferred embodiment of the present invention, a method for preparing the above-mentioned mesoporous carbon-supported praseodymium oxide catalyst is provided, which is suitable for synthesizing other mesoporous carbon-supported rare earth oxides, including mesoporous carbon-supported lanthanum oxide, mesoporous carbon-supported cerium oxide, mesoporous carbon-supported samarium oxide, mesoporous carbon-supported europium oxide, mesoporous carbon-supported gadolinium oxide, and mesoporous carbon-supported terbium oxide.
[0017] Technical Effects
[0018] The present invention uses mesoporous carbon as a carrier and Pr(NO3)3·6H2O as a praseodymium source to prepare an oxygen-defective nano-praseodymium oxide catalyst. The metal content of the mesoporous carbon-supported praseodymium oxide catalyst is 15-30wt.%. The praseodymium oxide nanoparticles in the catalyst prepared by the present invention are evenly dispersed and have uniform particle size. The catalyst can accelerate the sulfur reduction reaction of a lithium-sulfur battery and significantly improve the cycle stability of the battery.
[0019] The present invention discloses a mesoporous carbon-supported praseodymium oxide (PrO2 / OMC) catalyst and a preparation method thereof. The praseodymium oxide content of the PrO2 / OMC catalyst is 10-30wt.%, and the particle size is 2-5nm. The present invention utilizes coordination-assisted block copolymer self-assembly technology to synthesize, restricts the growth of praseodymium oxide nanoparticles in the mesoporous structure, and synthesizes stable mesoporous carbon-supported praseodymium oxide. The catalyst has a highly ordered two-dimensional hexagonal mesostructure, and the praseodymium oxide nanoparticles are small in size, uniformly distributed, and have good stability. The preparation method of the present invention is simple, low in cost, and the material has high activity, and has considerable development prospects in the field of rare earth functional material development and industrial catalysis.
[0020] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a transmission electron microscope and element distribution diagram of the mesoporous carbon-supported praseodymium oxide catalyst of Example 1 of the present invention;
[0022] Figure 2 is the X-ray diffraction spectrum of the mesoporous carbon-supported praseodymium oxide catalyst of Example 1 of the present invention;
[0023] Figure 3 is a transmission electron microscope image of the mesoporous carbon-supported praseodymium oxide catalyst of Example 3 of the present invention;
[0024] Figure 4 This is the X-ray diffraction spectrum of the mesoporous carbon-supported praseodymium oxide catalyst of Example 3 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0026] In the following description, specific details such as specific internal procedures and techniques are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present invention.
[0027] The present invention provides a method for preparing a mesoporous carbon-supported praseodymium oxide catalyst, comprising the following steps:
[0028] The triblock copolymer is used as a template, ethanol is used as a solvent, a low molecular weight phenolic resin produced by prepolymerization of phenol and formaldehyde is used as an organic precursor to provide a carbon source, and praseodymium salt hydrate is used as a metal source, and a mixed solution is obtained by stirring uniformly at a certain temperature;
[0029] The ethanol in the mixed solution is volatilized at a low temperature, and the carbon source and the metal source are co-assembled with the block copolymer through hydrogen bonding during the volatilization of the solvent ethanol to form a metal-polymer mesostructure, and then thermal polymerization occurs at a high temperature to fix the ordered mesophase of the metal-polymer;
[0030] The block copolymer is removed by low-temperature calcination, and then carbonized at high temperature to obtain a stable mesoporous carbon-supported rare earth praseodymium oxide catalyst, in which praseodymium oxide nanoparticles are uniformly distributed in the mesoporous pore walls of the carbon carrier.
[0031] Mesoporous carbon-supported praseodymium oxide catalyst has a highly ordered two-dimensional hexagonal mesostructure.
[0032] Among them, the triblock copolymer is F127, and F127 is (HO·(C2H4O) m ·(C3H6O) n H),
[0033] Example 1
[0034] This embodiment provides a method for preparing a mesoporous carbon-supported praseodymium oxide catalyst, the steps of which are as follows:
[0035] 1.5g F127 and 30mL ethanol were stirred in a heating mantle at 40℃ for 1h to obtain solution A. 324g Pr(NO3)3·6H2O and 10mL ethanol were added to the sample tube and ultrasonicated for 15min to obtain solution B. Then solution B was added to solution A and stirred for 30min. Subsequently, 5g PF was slowly added to the mixed solution and stirred for 30min. A small amount of the mixed solution was added to a dry petri dish to form a film. The petri dish was placed in an oven at 1℃min. -1 The temperature was raised to 40 °C at a rate of 1 °C / min and maintained for 24 h to allow the ethanol to evaporate slowly. -1 The temperature was raised to 80°C at a heating rate of 1°C / min and maintained for 24 hours for thermal polymerization. The assembled mesoscopic thin film material was obtained and then placed in a quartz boat for calcination after film scraping. -1 The temperature was raised to 350 °C at a rate of 1 °C min-1 and maintained for 3 h to remove the block copolymer. -1 The temperature was raised to 600°C at a heating rate of , and maintained for 2 h to allow the polymer to be carbonized and the metal salt to be reduced. After cooling to room temperature, the mixture was ground evenly to obtain a mesoporous carbon-supported praseodymium oxide catalyst.
[0036] Figure 1 and Figure 2 The transmission electron microscope, element distribution diagram and X-ray diffraction spectrum (XRD) of the mesoporous carbon-supported praseodymium oxide sample of Example 1 are shown respectively. Figure 1 , 2 As shown, it is shown that mesoporous carbon-supported praseodymium oxide is successfully synthesized, and the praseodymium oxide nanoparticles are evenly dispersed with a particle size of about 3 to 5 nm.
[0037] Catalytic performance test: The mesoporous carbon-supported praseodymium oxide catalyst was added to the lithium-sulfur battery. After the assembled button battery was cycled for 1000 cycles at a current density of 2C, the battery capacity decay rate per cycle was only 0.052%.
[0038] Examples 2-6 and Comparative Examples:
[0039] The operations of Examples 2 to 6 and the comparative examples are similar to those of Example 1, except that, as shown in Table 1, the amount of the drug added, the temperature and time of ethanol volatilization, the temperature and time of thermal polymerization, the carbonization temperature and other factors are changed; the operations of the comparative examples are similar to those of Example 1, except that the carbonization temperature is too high. As the carbonization temperature increases, the collapse of the mesoporous carbon pore wall becomes more serious, praseodymium oxide aggregates seriously, and the particle size increases. Please refer to Table 1 for the experimental conditions of Examples 2 to 6 and the comparative examples.
[0040] Table 1 Experimental conditions of Examples 1-6
[0041]
[0042]
[0043] It can be seen from the above embodiments that the present invention provides a method for preparing a mesoporous carbon-supported praseodymium oxide catalyst, in which praseodymium oxide nanoparticles are evenly distributed on the carbon carrier and have a particle size of 3 to 5 nm, and have excellent catalytic performance. The mesoporous carbon-supported praseodymium oxide catalyst is added to a lithium-sulfur battery, and the assembled button battery is cycled for 1000 cycles at a current density of 2C, and the battery capacity single-cycle attenuation rate is only 0.052%.
[0044] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a mesoporous carbon-supported praseodymium oxide catalyst, characterized in that: The following steps are involved: The triblock copolymer is used as a template, ethanol is used as a solvent, a low molecular weight phenolic resin produced by prepolymerization of phenol and formaldehyde is used as an organic precursor to provide a carbon source, and praseodymium salt hydrate is used as a metal source, and a mixed solution is obtained by stirring uniformly at a certain temperature; The ethanol in the mixed solution is volatilized at a low temperature, and the carbon source and the metal source are co-assembled with the block copolymer through hydrogen bonding during the volatilization of the solvent ethanol to form a metal-polymer mesostructure, and then thermal polymerization occurs at a high temperature to fix the ordered mesophase of the metal-polymer; The block copolymer is removed by low-temperature calcination, and then carbonized at high temperature to obtain a stable mesoporous carbon-supported rare earth praseodymium oxide catalyst, in which praseodymium oxide nanoparticles are uniformly distributed in the mesoporous pore walls of the carbon carrier. The mesoporous carbon-supported praseodymium oxide catalyst has a highly ordered two-dimensional hexagonal mesoscopic structure.
2. The method for preparing a mesoporous carbon-supported praseodymium oxide catalyst according to claim 1, characterized in that: The triblock copolymer is F127, and F127 is (HO·(C2H4O) m ·(C3H6O) n ·H), the added amount of F127 is 0.8-1.5g, the added amount of ethanol is 10-50mL, the added amount of PF is 5-8g, and the praseodymium salt hydrate is Pr(NO3)3·6H2O, and the added amount is 324g.
3. The method for preparing a mesoporous carbon-supported praseodymium oxide catalyst according to claim 1, characterized in that: The carbon source and the metal source co-assemble with the block copolymer through hydrogen bonding during the volatilization of the solvent ethanol. Specifically, under the induction of ethanol, the carbon source and the metal source assemble into an ordered mesoscopic structure, and then undergo thermal polymerization to stabilize the mesoscopic phase. The heating rate is 1-5 °C min -1 The temperature of ethanol volatilization is controlled at 30-50°C, the time of ethanol volatilization is controlled at 8-24h, the thermal polymerization temperature is 80-100°C, and the thermal polymerization time is controlled at 24-48h.
4. The method for preparing a mesoporous carbon-supported praseodymium oxide catalyst according to claim 2, characterized in that: F127 is first mixed with ethanol and stirred for 0.5 to 2 hours, and then an ethanol solution containing praseodymium salt is added. After the above liquids are evenly mixed, PF is added dropwise and then stirred for 0.5 to 1 hour. The reaction temperature of the above solution is controlled at 30 to 50°C.
5. The method for preparing a mesoporous carbon-supported praseodymium oxide catalyst according to claim 1, characterized in that: The block copolymer was removed by low-temperature calcination, and then a stable mesoporous carbon-supported rare earth praseodymium oxide catalyst was obtained by further high-temperature carbonization. The calcination atmosphere was N2, and the heating rate was 1-5 °C min -1 The temperature for removing the block copolymer is 200-400°C and maintained for 2-5 hours, and the temperature for high-temperature carbonization is 500-800°C and maintained for 1-3 hours.
6. The method for preparing a mesoporous carbon-supported praseodymium oxide catalyst according to claim 5, characterized in that: The praseodymium salt precursor solution was prepared by dissolving 324 g of praseodymium salt into 5-10 mL of ethanol solution and ultrasonicating for 5-30 min to obtain a uniform praseodymium salt ethanol solution.
7. A mesoporous carbon-supported praseodymium oxide catalyst prepared by the method according to any one of claims 1 to 6, characterized in that: The particle size of praseodymium oxide on the catalyst is within 10 nm and is evenly distributed in the mesoporous pore walls of the carbon carrier.
8. A method for preparing a mesoporous carbon-supported praseodymium oxide catalyst as described in any one of claims 1 to 6, which is suitable for synthesizing other mesoporous carbon-supported rare earth oxides, including mesoporous carbon-supported lanthanum oxide, mesoporous carbon-supported cerium oxide, mesoporous carbon-supported samarium oxide, mesoporous carbon-supported europium oxide, mesoporous carbon-supported gadolinium oxide, and mesoporous carbon-supported terbium oxide.